(3QSGdI aj UdGI GdXgQ HYO GdLeYIs - (3Ydj Hf Ydj GdTHQGedSj, CHh GdVjGA, fhQ GdOjf,J (B1087 (3g` s
(3ChdgG (B:s
(3bGd MeOkG def CeQ HGdJKHjJ ai GdCNHGQ hHYO , abO PcQ HYVge dMVQI GdhRjQ MSjf HGTG Cf UdGJfG (B_ (3eYGTQ GdTGaYjI (B_ (3GdXgQ LeGYI jhe GdLeYI dG CUd dgG s
(3BNQgG (B:s
(3Ydi Cf HYV GdMfajI fbd Edi Cf efge ef jUdi GdXgQ LeGYI HYO GdLeYI hCf YfOge ai UdGI GdXgQ HYO GdLeYI QSGdI dHYV GdeJCNQjf bGd GdeDda QMeI Gdgd JYGdi hgPG BNQ eG CQOfG EjQGOg ef gPg GdQSGdI s
(3GfJgi efgG eDdagG ai QeVGf (B1091(3g`s
(3HBNQgG fbd ef MGTjI TjN GdeDda ai TF Ydi TQM GdQedis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs